Efikasi Diri terhadap Kinerja Karyawan PDAM Tirtanadi Unit Instalasi Pengolahan Air Sunggal - Sri Ngayomi Yudha Wastuti (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2018)
His study aims to determine the effect of the self efficacy with employee performance at PDAM Tirtanadi.This study uses quantitative method with the number of samples as many as 40 people with try out system used, meaning that data have been taken in the test scale, re used as data for hypothesis testing. This research uses simple regression analysis method. Based on the data analysis obtained the results 1) There is a significant influence between self-efficacy on employee performance. It is shown by coefficient Freg = 97,611 where p <0,050. Indicates that the higher the self efficacy will be the better employee performance, and the lower the self-efficacy will be the worse employee performance. 2) There is a positive influence between self-efficacy on employee performance at PDAM Tirtanadi Sunggal Branch employee with 72% contribution. From these results it is known that there is still 28% influence from other factors on employee performance. 3) Another result is obtained from this research, which is known that the subject of this research the employees of Tirtanadi PDAM Sunggal Branch, has a very high self-efficacy with employee performance obtained is also quite high. This is known by looking at the empirical mean / self efficacy mean value (175.08) and the hypothetical average value (105). Furthermore, for employee performance it is known that the mean mean / empirical mean (85,88) and the hypothetical mean is (8).